Pendampingan Penggunaan Metode Lecture Vary bagi Guru dalam Peningkatan Hasil Belajar Siswa Sekolah Dasar MIN 5 Langkat - Emha Fidiyan Akhadi; Zaifaturridha Zaifaturridha; Rizky Ramadhan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
This community service activity aims to explore the Lecture Vary method used by madrasah teachers to improve elementary school student learning outcomes. In this effort, community service activities were carried out at MIN 5 Langkat using a quantitative approach with an experimental design. The research subjects were teachers and students at several MIN 5 Langkat elementary schools. Teachers were given training and assistance in using the Lecture Vary method for one semester. The research results showed a significant increase in student learning outcomes after teachers implemented the Lecture Vary method. The average student test score increased from 70 to 96,8 after one semester of using this method. These findings are consistent with previous research which states that interactive and varied teaching methods can improve student learning outcomes. This study concludes that the use of the Lecture Vary method for teachers has proven effective in improving the learning outcomes of MIN 5 Langkat students. It is hoped that this method can be adopted more widely by teachers to improve the quality of education.